Caesarean myomectomy: a descriptive study of clinical outcome - Pattanaik, Tapan; Pati, Basanta Kumar; Samal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective was to analyse the clinical outcome of caesarean myomectomy and to evaluate the safety of performing the procedure. Methods: A total of 23 cases of caesarean myomectomy, conducted in Institute of Medical Science and Sum Hospital Odisha, between January 2008 to December 2012 were analysed. Results: In this study, out of 23 cases one case needed hysterectomy and another one required relaparotomy. Puerperal pyrexia and sepsis was found in 8.6% cases and 60.8% cases had post-operative anaemia. Intra operative haemorrhage was more than 1000 ml in 82.6% cases though only30.4% cases required blood transfusion. Hospital stay in all patients was on average 8 days post-operatively. There was no maternal or perinatal mortality. Conclusion: Myomectomy is relatively safe during caesarean section in selected cases with expert hand.